Identification and Analysis of Zinc Efficiency-Associated Loci in Maize - Xu, Jianqin; Wang, Xuejie; Zhu, Huaqing; Yu, Futong (Frontiers in Plant Science, 2021)
Zinc (Zn) deficiency, a predominant micronutrient disorder in crops and human worldwide, reduces crop yields and adversely impacts human health. Despite numerous studies for physiological mechanism underlying Zn deficiency tolerance, its genetic basis of molecular mechanism is poorly understood. Zinc efficiency of twenty maize inbred lines was evaluated, and quantitative trait loci (QTL) analysis was performed in the recombination inbred line population derived from the most Zn-efficient (Ye478) and Zn-inefficient inbred line (Wu312) to identify the candidate genes associated with Zn deficiency tolerance. On this basis, we analyzed the expression of ZmZIP1 - ZmZIP 8. Thirteen QTLs for the traits associated with Zn deficiency tolerance were detected, explaining 7.6 - 63.5% of phenotypic variation. Genes responsible for Zn uptake and transport across membranes (ZmZIP3, ZmHMA3, ZmHMA4) were identified, which probably form a sophisticated network to regulate uptake, translocation and redistribution of Zn. Additionally, we identified genes involved in IAA biosynthesis (ZmIGPS) and auxin-dependent gene regulation (ZmIAA). Notably, high up-regulation of ZmZIP3 was found in Zn-deficient root of Ye478, not in that of Wu312. Besides, ZmZIP4, ZmZIP5 and ZmZIP7 were up-regulated in Zn-deficient roots of Ye478 and Wu312. Our findings provide a comprehensive insight into genetic basis of Zn deficiency tolerance.